Analisis Kinerja Keuangan pada PT. Bank Sinarmas Tbk yang Terdaftar pada Bursa Efek Indonesia Tahun 2019 – 2023 - Berkat Febrianto Lase; Pustika Ayuning Puri; Wahyu Purbo Santoso (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The strategic role of banking as an intermediary institution manifests through its ability to gather and channel funds from the public to support economic activities, ultimately enhancing the stability of the country's economic structure. The importance of banking health in the fund collection process requires a sound condition and banking services that attract public interest. Bank health evaluation can be conducted through various methods, including the CAMEL method covering capital, asset quality, management, earnings, and liquidity, as well as the RGEC method encompassing Risk Profile, Good Corporate Governance, Earnings, and Capital. Bank Sinarmas, as one of the public banks in Indonesia, has played a significant role in economic recovery through the distribution of People's Business Credit (KUR) and its success in maintaining the health of the banking sector. This research is descriptive with a quantitative approach, utilizing literature review and documentation as data collection techniques. The results of this study indicate that the financial condition of PT Bank Sinarmas Tbk from 2019 to 2023 can be classified as generally “healthy”. However, in terms of Asset Quality and Management aspects, it falls into the